Tracing expansive learning in computer-supported collaborative teaching. (April 2022) - Pareto, Lena; Willermark, Sara
Abstract: The theory of expansive learning is used in many studies to explore change in inter-organizational and non-traditional settings. However, long-term, fundamental expansive learning is challenging to study due to the amount of data and the duration of object formation over several years. Researchers call for methods for systematic analysis of expansive learning. This paper presents an approach to systematically trace expansive learning in teaching practice. The approach was developed during a three-year school development project in an elementary school context. The participatory project engaged 66 teachers and 32 researchers from Norway, Sweden, and Denmark aiming to develop innovative computer-supported collaborative teaching for a virtual Nordic classroom. The project was arranged in small inter-organizational teams that iteratively created, implemented, and evaluated novel ways of conducting computer-supported collaborative teaching. The project was immensely challenging with conflicts of interests and systemic contradictions between the inter-organizational collaborating teams, but when resolved cultivated the change in practice. To trace the formation of the teaching practice, we used an integrated approach combining the theory of expansive learning with a teaching practice framework, TPACK in situ, which helped us handle complexity and systematize the object formation, as well as examine the type of learning the teachers acquired.